Kepuasan Kerja dan Kinerja Karyawan pada Perusahaan Elektronik di Kawasan Industri Jababeka - Holong Saor Nababan (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2023)
Research aim: This study aims to find out, 1) the effect of transformational leadership, competence, and compensation on job satisfaction, and 2) the effect of transformational leadership, competence, compensation, and job satisfaction on performance. Design/Method/Approach: This type of research is quantitative. This study uses a survey approach that describes current conditions and answers questions about the characteristics of variables and the influence between variables. The sample selection was carried out by proportionate random sampling technique against 13 companies with 2.758 employees and a sample of 349. The analysis model used Structural Equation Modeling (SEM). Research Findings: The results of the analysis found that transformational leadership, competence, and compensation have a positive and significant effect on job satisfaction. Transformational leadership, competence, compensation, and job satisfaction positively and significantly affect employee performance. Theoretical Contribution / Originality: The results of this study enrich the theory of transformational leadership, especially in electronic companies. The results of this study also enrich the discussion of both concepts and theories of competence, compensation policies measuring job satisfaction, and performance in electronic companies. Practitioner/Policy implication: The results of this study as a basis for decision-making for stakeholders that the transformational leadership model is very appropriate to be applied to increase job satisfaction and employee performance to increase job satisfaction and employee performance. Increased competence and compensation will increase job satisfaction and employee performance. Employee job satisfaction will improve the performance of electronic companies. By implementing transformational leadership, and paying attention to competence, compensation, and job satisfaction, problems that occur specifically related to very high employee movement can be resolved properly. Research Limitations: This study has limitations. The research sample is an electronic company in the Jababeka Bekasi Industrial Estate, and it cannot describe the general characteristics of other companies, regions, or countries.